Social Microbial Transmission in a Solitary Mammal - Lauren Petrullo; Quinn Webber; Aura Raulo; Stan Boutin; Jeffrey E. Lane; Andrew G. McAdam; Ben Dantzer (Ecology Letters, 2025)
Microbial transmission is hypothesised to be a major benefit of sociality, facilitated by affiliative behaviours such as grooming and communal nesting in group‐living animals. Whether microbial transmission is also present in animals that do not form groups because territoriality limits interactions and prevents group formation remains unknown. Here, we investigate relationships among gut microbiota, population density and dynamic behavioural and spatial measures of territoriality in wild North American red squirrels ( Tamiasciurus hudsonicus ). Periods of high population density predicted population‐level gut microbial homogeneity but individual‐level diversification, alongside changes in obligately anaerobic, non‐sporulating taxa indicative of social transmission. Microbial alpha‐diversity increased with more frequent territorial intrusions, and pairs with stronger intrusion‐based social associations had more similar gut microbiota. As some of the first evidence for social microbial transmission in a solitary system, our findings suggest that fluctuations in density and territorial behaviours can homogenise and diversify host microbiomes among otherwise non‐interacting animals.

Past and future wheat yield losses in France’s breadbasket - Rogério de S. Nóia-Júnior; Pierre Martre; Jean-Charles Deswarte; Jean-Pierre Cohan; Marijn Van der Velde; Heidi Webber; Frank Ewert; Alex C. Ruane; Tamara Ben-Ari; Senthold Asseng (Field Crops Research, 2025)

Progress in understanding of Indian Ocean circulation, variability, air–sea exchange, and impacts on biogeochemistry - Helen E. Phillips; Amit Tandon; Ryo Furue; Raleigh Hood; Caroline C. Ummenhofer; Jessica A. Benthuysen; Viviane Menezes; Shijian Hu; Ben Webber; Alejandra Sanchez-Franks; Deepak Cherian; Emily Shroyer; et al. (Ocean Science, 2021)
Over the past decade, our understanding of the Indian Ocean has advanced through concerted efforts toward measuring the ocean circulation and air–sea exchanges, detecting changes in water masses, and linking physical processes to ecologically important variables. New circulation pathways and mechanisms have been discovered that control atmospheric and oceanic mean state and variability. This review brings together new understanding of the ocean–atmosphere system in the Indian Ocean since the last comprehensive review, describing the Indian Ocean circulation patterns, air–sea interactions, and climate variability. Coordinated international focus on the Indian Ocean has motivated the application of new technologies to deliver higher-resolution observations and models of Indian Ocean processes. As a result we are discovering the importance of small-scale processes in setting the large-scale gradients and circulation, interactions between physical and biogeochemical processes, interactions between boundary currents and the interior, and interactions between the surface and the deep ocean. A newly discovered regional climate mode in the southeast Indian Ocean, the Ningaloo Niño, has instigated more regional air–sea coupling and marine heatwave research in the global oceans. In the last decade, we have seen rapid warming of the Indian Ocean overlaid with extremes in the form of marine heatwaves. These events have motivated studies that have delivered new insight into the variability in ocean heat content and exchanges in the Indian Ocean and have highlighted the critical role of the Indian Ocean as a clearing house for anthropogenic heat. This synthesis paper reviews the advances in these areas in the last decade.

Developing effective management solutions for controlling stinking passionflower (Passiflora foetida) and promoting the recovery of native biodiversity in Northern Australia - Tommaso Jucker; Vicki Long; David Pozzari; Dan Pedersen; Ben Fitzpatrick; Paul B. Yeoh; Bruce L. Webber (Biological Invasions, 2020)